Marked improvement of Churg–Strauss syndrome neuropathy by intravenous immunoglobulin and cyclophosphamide. Issue 2 (14th April 2014) - Umeda, Akira; Yamane, Tateki; Takeuchi, Jin; Imai, Yasuo; Suzuki, Keisuke; Yumura, Wako
Abstract A 42‐year‐old Japanese man developed Churg–Strauss syndrome 7 years after being diagnosed with chronic eosinophilic pneumonia. Prominent eosinophilia, subcutaneous nodules, and neuropathy in the left leg were seen. A pathological diagnosis of necrotizing vasculitis was determined by a biopsy of a subcutaneous nodule. The leg pain was severe and there was prominent atrophy of the thigh and calf, but the muscle weakness was mild. Serum anti‐myeloperoxidase anti‐neutrophil cytoplasmic antibody was positive. Because the initial treatment with an intravenous methylprednisolone pulse at 1 g/day for 3 days was not sufficient, a onetime treatment with intravenous cyclophosphamide at 15 mg/kg and intravenous immunoglobulin therapy (IVIG) at 400 mg/kg/day for 5 days were administered. Peripheral eosinophilia improved and the leg pain significantly improved. IVIG was repeated 1 month later and symptoms gradually improved further. The early diagnosis of Churg–Strauss syndrome and the early initiation of IVIG with cyclophosphamide were thought to be important.